LESSON LEARNING ENERGY SECURITY FROM SWEDEN TO INDONESIA (SYSTEMS THINKING) - Dwiyono, Ari; Sutrasna, Yudi; Navalino, Djoko Andreas (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The energy crisis is being felt in Europe including Sweden due to the halt in gas supplies from Russia. Russia's infusion of Ukraine caused European countries to impose economic sanctions on Russia and the feedback Russia provided was to stop energy supplies to European countries. Energy scarcity causes inflation in various countries including Sweden. This shows that the discussion of energy and economics are two inseparable things. The purpose of this study is to explain how the concept of the system thinks of the occurrence of an energy crisis caused by the Russian and Ukrainian wars and describes the concept of developing the necessary energy technology as a state defense effort from the point of view of the defense economy and make a lesson learning for Indonesia. The method used is a descriptive qualitative method with a literature study research approach using a system thinking model. The result of this paper is a picture of the flow of the energy crisis and the development of energy technology that affects the country's defense caused by the interruption of gas supply which causes the energy crisis in Sweden to require the search for alternative energy and the development of energy technology to support the availability of energy security in the country as an effort to defend the country.